2019
DOI: 10.3390/w11102128
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of the Microbial Community in a Contaminated Aquitard below an Industrial Zone

Abstract: The industrial complex Neot Hovav, in Israel, is situated above an anaerobic fractured chalk aquitard, which is polluted by a wide variety of hazardous organic compounds. These include volatile and non-volatile, halogenated, organic compounds. In this study, we characterized the indigenous bacterial population in 17 boreholes of the groundwater environment, while observing the spatial variations in the population and structure as a function of distance from the polluting source. In addition, the de-halogenatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…This result was in accordance with previous studies [42,48,49] that indicate microbial communities were affected by soil pH. Second, the heavy metal may cause a shift in the bacteria composition [44,50,51]. Song et al, [52] suggested that the heavy metals (Cd, Cu and Zn) change the microbial biomass and the bacterial community.…”
Section: Plos Onesupporting
confidence: 91%
“…This result was in accordance with previous studies [42,48,49] that indicate microbial communities were affected by soil pH. Second, the heavy metal may cause a shift in the bacteria composition [44,50,51]. Song et al, [52] suggested that the heavy metals (Cd, Cu and Zn) change the microbial biomass and the bacterial community.…”
Section: Plos Onesupporting
confidence: 91%
“…The pipes' spacing influences the temperature field and closure time of the frozen wall. Balaban et al (2019) [10] present the results of field research related to microbial community in a fractured chalk aquitard below the industrial zone Neot Hovav in Israel, which is polluted by a wide variety of hazardous organic compounds. The spatial variations in indigenous bacterial population and their structure were assessed as a function of distance from the polluting source.…”
Section: Special Issue Overviewmentioning
confidence: 99%
“…The two brominated flame retardants (BFR), i.e., dibromoneopentyl glycol (DBNPG) and tribromoneopentyl alcohol (TBNPA), are from the abundant pollutants found in the groundwater underlying the Neot Hovav industrial zone, Israel [3]. Numerous organic compounds pollute this aquitard and sustain a rich microbial community, which is spatially changing due to contamination [4]. BFRs are known for their widespread adverse health effects, with TBNPA being defined as a moderate aquatic and human hazard by the EPA [5] and DBNPG defined carcinogenic in rodents [6].…”
Section: Introductionmentioning
confidence: 99%